Electrochemical upgrading of depolymerized lignin: a review of model compound studies. Issue 8 (14th April 2021) - Garedew, Mahlet; Lam, Chun Ho; Petitjean, Laurene; Huang, Shuquan; Song, Bing; Lin, Fang; Jackson, James E.; Saffron, Christopher M.; Anastas, Paul T.
Abstract : This review addresses advancements and challenges in the use of electrochemical methods as a means of upgrading lignin-derived model compounds to value-added products. Abstract : A sustainable bio-based future necessitates the utilization of all components of biomass including lignin, which is the second most abundant biopolymer and a source of renewable aromatics. While its use for low value fuel and power production is well established, deriving further value from it via various conversion and upgrading schemes can help enable economically and environmentally sustainable and profitable biorefineries and provide opportunities to implement the principles of Green Chemistry to minimize negative environmental impacts. As lignin is converted to phenolic monomers, dimers, and oligomers via various conversion methods, electrocatalytic upgrading of these lignin-derived intermediates offers a sustainable way to integrate renewable energy sources such as wind and solar with biomass conversion methods to make valuable products. Using this strategy, abundant low-value lignin intermediates can be used to capture excess renewable electricity in the form of chemical bonds. Furthermore, this process allows for fine tuning of selectivity via the control of electrical potential and avoids elevated temperatures and pressures, further reducing energy inputs. Herein, we present a review of recent electrochemical studies of lignin-derived model compounds. Both oxidative and reductive methods for electrocatalytic upgrading of lignin-relevant monomers are discussed as well as electrocatalytic cleavage of lignin dimers representing specific linkages. Towards framing this technology's future implementation, we also provide a perspective on the main challenges and opportunities in this growing field.